The antipsychotics functional index (AFI) in schizophrenia - Marinescu, Gabriel-Cristian; Ifteni, Petru Iulian; Teodorescu, Andreea; Georgescu, Radu (Frontiers in Pharmacology, 2025)
Schizophrenia can lead to significant and long-lasting deficits in patient functionality. The present study proposes a theoretical index that predicts the ability of an antipsychotic to improve the functionality of patients with schizophrenia. An advantage of this theoretical index is that it directly compares 29 first- and second-generation antipsychotics. This theoretical index, named the Antipsychotics Functional Index (AFI), was constructed considering factors such as pharmacodynamics, pharmacokinetics, pharmaceutical form, ease of administration, and safety aspects. A good antipsychotic ranking based on the proposed index results from combining the partial dopaminergic agonist mechanism and a lower frequency of administration. The top-ranked antipsychotic is aripiprazole long-acting injection (LAI) administered every 2 months, 6 weeks, or 1 month, which is the only antipsychotic D2 partial agonist with an LAI formulation. It is followed by paliperidone LAI administered every 6 months. This antipsychotic has the least frequent administration schedule. According to the AFI, the most favorable antipsychotics for functionality are generally second-generation LAI antipsychotics. The D2 partial agonist mechanism has a pharmacodynamic advantage. Based on this functionality index, psychiatrists could select the most suitable antipsychotic for each patient, with the ultimate goal of helping the patient achieve their maximum potential.